2013
DOI: 10.1128/jcm.00302-13
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Fluorescence In Situ Hybridization Method Using Peptide Nucleic Acid Probes for Detection of Helicobacter pylori Clarithromycin Resistance in Gastric Biopsy Specimens

Abstract: h Here, we evaluated a previously established peptide nucleic acid-fluorescence in situ hybridization (PNA-FISH) method as a new diagnostic test for Helicobacter pylori clarithromycin resistance detection in paraffin-embedded gastric biopsy specimens. Both a retrospective study and a prospective cohort study were conducted to evaluate the specificity and sensitivity of a PNA-FISH method to determine H. pylori clarithromycin resistance. In the retrospective study (n ‫؍‬ 30 patients), full agreement between PNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Similarly, PNA also has a restricted flexibility of probe design as PNA cannot be mixed with nucleotide monomers like DNA, LNA, or UNA. In this case, and because there are no guidelines related to the minimum ΔG°, we based our design on our extensive experience in working with these probes (Guimaraes et al 2007;Cerqueira et al 2011Cerqueira et al , 2013. In contrast, LNA, 2′OMe, and UNA bases can be positioned anywhere within an oligonucleotide sequence, which means that the design is much more flexible and that probe fine-tuning is possible (You et al 2006).…”
Section: Probe Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, PNA also has a restricted flexibility of probe design as PNA cannot be mixed with nucleotide monomers like DNA, LNA, or UNA. In this case, and because there are no guidelines related to the minimum ΔG°, we based our design on our extensive experience in working with these probes (Guimaraes et al 2007;Cerqueira et al 2011Cerqueira et al , 2013. In contrast, LNA, 2′OMe, and UNA bases can be positioned anywhere within an oligonucleotide sequence, which means that the design is much more flexible and that probe fine-tuning is possible (You et al 2006).…”
Section: Probe Designmentioning
confidence: 99%
“…However, it has been shown that for DNA sequences, this discrimination is often difficult to achieve (Kubota et al 2006). More recently, other types of synthetic nucleic acids such as peptide nucleic acid (PNA) and locked nucleic acids (LNA) have been used in FISH with very promising results (Guimaraes et al 2007;Mook et al 2007;Tavares et al 2008;Campbell and Wengel 2011;Almeida et al 2013;Cerqueira et al 2013). To understand the specificity of these novel molecules towards DNA and RNA, several thermal dissociation studies have been conducted to analyze the effects of mismatches on duplex stability (Owczarzy et al 2011;Yan et al 2012;Matsumoto et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work demonstrates the effectiveness of using PNA-FISH to distinguish between 2 metabolically and genetically distinct Dehalococcoides strains. In previous works, PNA-FISH has been shown to surpass standard DNA-FISH in terms of robustness, and is now starting to be commercially available to detect microorganisms in clinical samples [Cerqueira et al, 2013]. Hence, the method can have strong implications for the monitoring and discrimination of Dehalococcoides populations in laboratory cultures and at contaminated sites.…”
Section: Application Of Probes To Mixed Culturesmentioning
confidence: 99%
“…Tests to determine antibiotic susceptibility include direct culture of gastric mucosal biopsies and molecular assays such as PCR or peptide nucleic acid-fluorescence in situ hybridization of either gastric mucosa or stool [1,2,3]. The recent Maastricht IV/Florence Consensus Report advocates performing cultures of gastric biopsies with antibiotic susceptibility testing prior to administering first-line clarithromycin (CLA)-based treatment in areas of high resistance, prior to second-line treatment if an upper endoscopy is scheduled and prior to third-line therapy in all other cases [4].…”
Section: Introductionmentioning
confidence: 99%